Constructing purchase intention model for foreign banks operating within Indonesia - Muchtar, Fatimah; Kingshott, Russel; Wong, David; Laksamana, Patria (Electronic Business Management Society, 2011)
Indonesia is a developing economy and reliant upon foreign direct investment to increase its economic outlook. However, being located in a strategic position between Asia, Australasia and Oceania has made it an attractive proposition for foreign banks such as Citibank, HSBC, Standard Chartered. Despite this there are many market and regulatory challenges facing foreign banks operating within Indonesia. To gain a competitive edge they must clearly understand how the many cultures, values, norms, behaviours, mindsets and consumer lifestyles within Indonesia can be used to help drive strategy. Unfortunately, very little is known about Indonesian consumption preferences for foreign bank offerings. By drawing upon utility theory (UT) the main aim of this manuscript is to construct a purchase intention model that explains the effects of country of origin, trust and social consciousness upon purchase intentions of foreign bank offerings. Based upon the conceptual model we discuss a number of implications.